Analisis nilai tambah produk gula aren di desa Ogowele Buga Kabupaten Tolitoli - Bustam Bustam; Moh. Sabrab A (Insight Management Journal, 2021)
This study aims to determine the added value of palm sugar processing in Ogowele Buga Village, Dondo District, Tolitoli Regency. The data analysis method used is the Hayami method added value analysis. The results showed that the added value obtained by Palm Sugar was Rp. 1.300/kg or 52%, and the profit received by farmers is Rp. 1,000/kg or 40% means that every Rp.100 of the value of palm sugar products contains an added value of 52%. To increase the added value of the products produced, farmers need to continue to make efficiency, especially in terms of costs and raw materials used. The added value of palm sugar products according to this study is very feasible to be developed, but because the input of the main ingredients available is very little, the profits generated by farmers are also small, therefore a large number of main ingredient inputs are needed so it is recommended for the local government if you want to develop palm sugar products in Indonesia. Ogowele Buga Village, a massive palm tree planting program can be carried out in Ogowele Buga Village.